I change my mind to get better: Process tracing-based microanalysis of food choice processes reveals differences between anorexia nervosa and bulimia nervosa during inpatient treatment. (1st January 2022) - Georgii, Claudio; Eichin, Katharina Naomi; Richard, Anna; Schnepper, Rebekka; Naab, Silke; Voderholzer, Ulrich; Treasure, Janet; Blechert, Jens
Abstract: Food choice and its underlying processes is understudied in bulimia nervosa (BN) and anorexia nervosa (AN). Thus, we examined cognitive processes during food choice through mouse tracing in AN ( n = 36) and BN ( n = 27) undergoing inpatient treatment. Both patient groups and matched healthy controls (HC, n = 59) made 153 binary food choices before rating all foods on their liking and calorie density. Choice outcomes and corresponding mouse movements were modelled as a function of inpatient treatment stage in our analyses. Compared to patients with BN and HC, those with AN showed a clear calorie avoidance on most trials. Yet, mouse paths in AN patients early in treatment, revealed a late direction reversal ('change of mind', CoM) on high-calorie choices. AN patients later in treatment, by contrast, showed fewer CoM alongside more choices for – and liking of – high-calorie foods. Patients with BN showed more CoM trials during low-calorie choices and low-calorie choices were more frequent in patients later in treatment. Thus, relative to patients early in treatment, patients who are later in treatment show less of the overall group pattern of consistently choosing low-calorie food (AN) or high-calorie food (BN). Less cognitive regulation (fewer CoM trials) went along with higher liking for high-calorie foods in AN. These cross-sectional differences between AN early and late in treatment might reflect the formation of healthier habits. In addition, clear patient group differences suggest more specific treatment strategies.